التعليم الدينية الإسلامية في سجن سيمفنج رنجم بولاية جوهر - Muhammad Azali Bin Abdan (Kolej Universiti Islam Malaysia, 2011)
The objective of this research, titled "The Islamic Teaching at Penjara Simpang Rengam, Johor" to know profoundly the application of Islamic religious teachings which is applied at this prison either it should be increased and arranged for more effective and influence among the prisoners. Then, for this research, the writer used two-methodology embodying library research and field work which most of the references were taken from KUIM library as well from JAKIM and UKM library. Meanwhile the sources for the field work were taken from the Department Of Simpang Rengam Prison by interviewing and taking the printed sources. Most of the prisoners do not have a truly understanding and knowledge concerning Islamic thought. Needless to say, Islam is a good guidance to all mankind in order to achieve a proper place, prosperity and harmony living. The result from the research shows, in the ages of the beginning of Islam, prison was established with its own concept which differed from prison nowadays. It also shows that the Islamic thought at this prison have its own well-structured methods. It is crucial to ensure that all of the prisoners could gain a better understanding and improvement from the lesson. Overall, the result shows the effectiveness of preservation system among the prisoner which has been done that simultaneously teaches and trained them to be a responsible and good citizen.